KATECHETA W ŚRODOWISKU SZKOŁY WOBEC PROBLEMÓW DEMONOLOGII - Niesporek, Marcin (Studia Pastoralne, 2023)
The presence of a religion teacher at school becomes a chance to evangelise both students and teachers. They all come from different backgrounds and have varying experience of God. The article A Religion Teacher in a School Environment in the Face of a Demonology Issue is an attempt to show a religion teacher’s tasks which he can undertake during religious instruction lessons and during informal contacts with other teachers. These tasks are not focused only on spreading the Gospel. But also on making young people aware of spiritual threats connected with wearing satanist symbols and promoting satanism, organizing Halloween, propagating magic. The article proves that the school curriculum for catechism does not underline the threats sufficiently. It contains suggestions of improving the content of the subject in this aspect and also of fuller use of the priest teacher’s presence at school.